Lithium-doped calcium silicate scaffolds induce miR-130a-rich M2 macrophage EV-accelerating diabetic bone healing through angiogenesis–osteogenic coupling and mitochondrial repair - Ting-You Kuo; Cheng-Yu Chen; Yen-Hong Lin; Der-Yang Cho; Tsung-Li Lin; Ming-You Shie (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Hydraulic conductivity and the associated xylem anatomy as reliable predictors of tree productivity for Populus species along the fast-slow spectrum - Attaullah Khan; Xue-Wei Gong; Jing-Jing Guo; Cheng-Lin Yuan; Shen-Hao Song; Zhong-Yi Pang; Yan-Hui Peng; Xue-Kai Sun; Guang-You Hao (Agricultural and Forest Meteorology, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Valorization of baghouse dust from lime industry through carbonation processes - Hung-Chieh Liang; Cheng-You Lin; Hsing-Jung Ho; Cheng-Han Lee (Waste Management, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Chemical constituents and ferroptosis inhibitory activity of the deep-sea-derived fungus Penicillium citrinum W24 - Cheng-You Lin; Yuan Wang; Tai-Zong Wu; Rong Chao; Zheng-Biao Zou; Li-Sheng Li; Tian-Hua Zhong; Xian-Wen Yang (Natural Product Research, 2026)

Introducing Double-Moment Warm Rain Physics into the Goddard 4ICE Microphysics Scheme - Kao-Shen Chung; Yu-Jyun Liou; Cheng-Rong You; Zhao-Cheng Zeng; Pay-Liam Lin; Donghai Wang; Wei-Kuo Tao; Stephen Lang; Takamichi Iguchi; Adrian Loftus; Jiun-Dar Chern (Asia-Pacific Journal of Atmospheric Sciences, 2026)
In this study, a new double-moment warm rain Goddard 4ICE scheme (GCEDM) is developed based on the Goddard 4ICE single-moment (GCESM) scheme and then tested using idealized 2D squall line and 3D supercell simulations. The addition of the total number concentrations for cloud water ( $$\:N_{TC}$$ ) and rainwater ( $$\:N_{TR}$$ ) enables this new scheme to simulate more diverse raindrop size distributions, making it more realistic. GCEDM has similar overall thermal and dynamic characteristics to GCESM but produces higher evaporation rates, predicted particle number concentrations, and mass mixing ratios than GCESM, leading to stronger cold pools than with GCESM. In addition, comparisons are made versus the Weather Research and Forecasting Model Double-Moment Microphysics 7-class scheme (WDM7), which was also improved from a single-moment 4-class ice scheme to a double-moment warm-rain scheme. WDM7 also shows a stronger cold pool, but the system characteristics and microphysical processes are quite different from the single-moment version of this scheme.

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

Boosting ammonia-fed solid oxide fuel cell performance via high-entropy alloy anode surface modification - Nasima Khatun; Cheng-Ju Lin; Jia-You Lin; Sridharan Balu; Shi-Shin Yang; Sea-Fue Wang; Thomas C.-K. Yang (Fuel, 2026)

Antioxidant capability of peanut shell extracts obtained using an ethanol–ammonium sulfate two-phase system - Yung-Sheng Lin; Cheng-Kun He; Yun-En Jian; Ming-Ren Chen; Tz-Feng Lin; Cheng-You Chen; Wei-Hsun Wang (Biomass and Bioenergy, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

The study on soot formation and spray ignition characteristics of conventional aviation fuels: Jet A-1 and JP-5 - Jhe-Kai Lin; You-Cheng Huang; Wei-Cheng Wang; Hiew Mun Poon; Meng-Choung Chiong (Fuel, 2026)

Self-reporting and high-energy supercapacitors enabled by electrochromic ZnCo-S@CuFe-LDH heterostructures via interfacial engineering - Jiale Hou; Zhenghu Zhu; Haofeng Lu; Hecong Wang; Cheng Chen; Xinfeng Wu; Yonghou Xiao; Wanghui Wei; Minjie Xue; Lexing You; Xinzhou Ma; Donghai Lin (Chemical Engineering Journal, 2026)

The role of circulating metallothionein 1 in voriconazole-associated hepatotoxicity - Xiaowen Wang; Lina Wang; Xi You; Changsheng Jia; Qian Wang; Lin Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Dimeric citrinins diversity revealed by the deep-sea-derived Penicillium citrinum W23 - Tai-Zong Wu; Zhi-Hui He; Cheng-You Lin; You Li; Zheng-Biao Zou; Chun-Lan Xie; Tian-Hua Zhong; Xian-Wen Yang (Phytochemistry, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

A new chemical marker method for determining heating patterns in microwave pasteurization - Xu Zhou; Huimin Lin; Cheng-You Wu; Shyam S. Sablani; Juming Tang (Journal of Food Engineering, 2025)

Response of black tea powder and its fermentation products on growth performance, antioxidant capacity, and gut microbiota of Cherax quadricarinatus - Xian-Jing Zhang; Jiao-Fen Lin; Cheng-Jian Wu; Jie-Quan Xie; You-Shu Cai; Xu-Yin Lin (Frontiers in Marine Science, 2025)
Introduction The overuse of antibiotics in aquaculture has raised concerns, necessitating the exploration of sustainable alternatives. This study evaluated tea-derived additives as potential substitutes. Methods This study evaluated the effects of black tea powder (BTP) and black tea powder-probiotics mixed fermentation product (TPMFP) on Cherax quadricarinatus growth, antioxidant capacity, and gut microbiota. Cherax quadricarinatus were fed diets supplemented with BTP (1–6%) or TPMFP (2%) for 84 days. Results The addition of BTP (<2%) to the feed enhances the weight, carapace length, and muscle protein content of Cherax quadricarinatus , while higher doses (>3%) showed adverse effects. Moreover, the addition of BTP (1%-6%) can significantly reduce the muscle content of CHO, TG, and HDL (P<0.05). The TPMFP group exhibited the highest muscle protein content and significantly elevated hepatopancreatic SOD, GSH-PX, and AKP activities (P < 0.05), indicating improved antioxidant capacity. Gut microbiota analysis revealed dose-dependent shifts, with Proteobacteria dominating (>70%) and Aeromonas increasing with BTP levels. TPMFP significantly increased the α-diversity indices (richness and evenness) of the gut microbiota. The Mantel test confirmed the relationship between the antioxidant function of the microbial community, with Proteobacteria positively correlated with GSH-PX/SOD, while Fusobacteria and Tensionella negatively correlated with antioxidant enzyme activity. Discussion This study provides a foundation for using tea-derived additives as a sustainable alternative to antibiotics in aquaculture.In the future, metagenomic analysis of key metabolic pathways can be combined to optimize the mechanistic explanation of the application and efficacy of BTP and TPMFP.

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Mercerized bacterial cellulose/chitosan/waterborne polyurethane composites for sustainable and effective food preservation packaging - Cheng-Ying Li; Jhu-Lin You; I-Tseng Liu; Annisa Istiqomah; Ying-Chih Liao (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Quantify the effects of water-soluble salts and available fractions of nutrient elements on mobility of cadmium in paddy soil: A case study of the Pearl River Delta - Changchen Huang; Weikang Sheng; Qingye Hou; Zhongfang Yang; Tao Yu; Yuanhang You; Kun Lin; Cheng Li (Journal of Cleaner Production, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Correlation between pyrethroid knockdown resistance and mutation frequency of voltage-gated sodium channel and its application in Aedes aegypti management - Hsin-Hua Lin; Zhong-Tai Li; Hau-You Tzeng; Cheng Chang; Shu-Mei Dai (Pesticide Biochemistry and Physiology, 2024)

Yield loss of inferior crop species and its physiological mechanism in a semiarid cereal-legume intercropping system - Wei Wang; Jian-Hua Zhao; Meng-Ying Li; Wei Zhang; Muhammad Maqsood Ur Rehman; Bao-Zhong Wang; Fazal Ullah; Zheng-Guo Cheng; Li Zhu; Jin-Lin Zhang; Hong-Yan Tao; Wen-Ying Wang; et al. (European Journal of Agronomy, 2024)

The role of oxide supports in constructing plasma-treated gold nanocatalysts for visible light photocatalytic oxidation of CO - Bin Zhu; Chong-Hua Zhong; Bang-You Jia; Tie Li; Jing-Lin Liu; Ye-Cheng Li; Yi-Min Zhu (Chemical Engineering Journal, 2024)

Late Holocene Climate Warming Events and Their Linkage to Hydraulic Engineering on the Coast of Hangzhou Bay, East China - Xunpeng Li; Xiaolei You; Sen Lin; Wentong Zhang; Zeen Cheng; Zhanghua Wang (Journal of Marine Science and Engineering, 2023)
The coastal lowlands in East China are very sensitive to climate change and marine disasters, and much large-scale hydraulic engineering was recorded in the historical documents of the Late Holocene. In this study, AMS 14C and OSL were used to date three sedimentary profiles from the north and south coasts of inner Hangzhou Bay, and grain size and geochemical analyses including organic carbon, macro-elements, and alkaline earth metals were performed, while hydraulic engineering records in historical documents were compiled, in an attempt to reveal the sedimentary records of extreme climatic and hydrological events over the past 3000 years and to probe into the correlation between them and hydraulic engineering. The results show that the intensified chemical weathering during ca. 200 BCE to 900 CE in East China corresponded to the warm and humid climate during the Qin-Han and Sui-Tang dynasties. Salinity intrusion with rising local water levels occurred in the lowland plains along the south coast of Hangzhou Bay from 120 to 895 CE. Low-salinity water intrusion from 32 to 488 CE was also recorded in the stratigraphy of lowland plains along the north coast of Hangzhou Bay. The sedimentary records of the East Tiaoxi River basin show river floods about 2000 years ago. The above sedimentary records indicate that the relative sea level rose in the Hangzhou Bay area during the Qin-Han and Sui-Tang Warm Periods, resulting in frequent salinity intrusion and river floods, which coincided with the historical records of hydraulic engineering such as the construction of seawalls, river levees, and the enclosure of lakes for restoration of river floods during the Han and Tang dynasties. Such coincidence reflects that climate change profoundly affected the hydrological environment of the coastal areas in East China as well as the response of the human societies.

Binary-1D/2D nanomaterial-functionalization toward strong, stretchable, and anti-freezing electrically conductive organohydrogels for self-powered operation monitoring of robotic hand - Jie Zhou; Bo Tang; Dong Li; Cheng-Wei You; Yu-Yao Zhao; Lin-Yue Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Ketamine exerts dual effects on the apoptosis of primary cultured hippocampal neurons from fetal rats in vitro - Guo-Hua Wu; Que-Hui Guo; Xiao-Dong Xu; Jian-Chang Lin; Gui-Ting You; Cai-Hou Lin; Liang-Cheng Zhang (Metabolic Brain Disease, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Enhancement of chromium (VI) removal and power generation by adding biochar to a single-medium sediment-based microbial fuel cell - Chi-Wen Lin; You-Cheng Jhan; Ting-Jun Zhu; Shu-Hui Liu (Journal of Water Process Engineering, 2023)

The decadal abrupt change in the global land vapor pressure deficit - Mengqi Cheng; Zhiyan Zuo; Zouxing Lin; Qinglong You; Huan Wang (Science China Earth Sciences, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

In vitro and in vivo anti-tumor activity of Coenzyme Q0 against TWIST1-overexpressing HNSCC cells: ROS-mediated inhibition of EMT/metastasis and autophagy/apoptosis induction - Hsin-Ling Yang; Li-Wen Chiu; Yi-An Lin; Sudhir Pandey; Chithravel Vadivalagan; Jiunn-Wang Liao; Yugandhar Vudhya Gowrisankar; Hui-Jye Chen; Hui-Yi Lin; You-Cheng Hseu (Toxicology and Applied Pharmacology, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Effectiveness of Combined Exercise and Physiotherapy Intervention in Improving Functional Activity of Patients with Knee Osteoarthritis in Muslim Pray Movements - Rakhmad Rosadi; Po-Ting Wu; Yu-Lin You; Li-Chieh Kuo; Cheng-Feng Lin (Journal of Medical and Biological Engineering, 2023)

Coenzyme Q0 defeats NLRP3-mediated inflammation, EMT/metastasis, and Warburg effects by inhibiting HIF-1α expression in human triple-negative breast cancer cells - Hsin-Ling Yang; Ping-Yu Lin; Chithravel Vadivalagan; Yi-An Lin; Kai-Yuan Lin; You-Cheng Hseu (Archives of Toxicology, 2023)

Cytotoxic steroidal glycosides from the rhizomes of Paris polyphylla var. yunnanensis - Yang Liu; Mei-You Liu; Lin-Lin Bi; Yun-Yuan Tian; Peng-Cheng Qiu; Xiao-Ying Qian; Min-Chang Wang; Hai-Feng Tang; Yun-Yang Lu; Bang-Le Zhang (Phytochemistry, 2023)

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation - Lei Jiang; Cheng‐Yue Liu; Guoxin Cui; Lin‐Tao Huang; Xiao‐Lei Yu; You‐Fang Sun; Hao‐Ya Tong; Guo‐Wei Zhou; Xiang‐Cheng Yuan; Yi‐Si Hu; Wen‐Liang Zhou; Manuel Aranda; et al. (Molecular Ecology, 2023)
Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat‐acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonstrated higher bleaching resistance and better photosynthetic and autotrophic performance in heat‐exposed larvae from acclimated adults compared to unacclimated adults. RNA‐seq revealed strong cellular stress responses in larvae from heat‐acclimated adults that could have been effective in rescuing host cells from stress, as evidenced by the widespread upregulation of genes involved in cell cycle and mitosis. For symbionts, a molecular coordination between light harvesting, photoprotection and carbon fixation was detected in larvae from heat‐acclimated adults, which may help optimize photosynthetic activity and yield under high temperature. Furthermore, heat acclimation led to opposing regulations of symbiont catabolic and anabolic pathways and favoured nutrient translocation to the host and thus a functional symbiosis. Notwithstanding, the improved heat tolerance was paralleled by reduced light‐enhanced dark respiration, indicating metabolic depression for energy saving. Our findings suggest that adult heat acclimation can rapidly shift thermal tolerance of brooded coral larvae and provide integrated physiological and molecular evidence for this adaptive plasticity, which could increase climate resilience. However, the metabolic depression may be maladaptive for long‐term organismal performance, highlighting the importance of curbing carbon emissions to better protect corals.

The extract from aerial part of Scutellaria baicalensis regulates gut microbiota in rabbit fish: Replacement of antibiotic fighting against pathogenic bacteria - Yi-Teng Xia; Edwin Hok-Chi Cheng; Huai-You Wang; Lynn Hoi-Lam Zhang; Sheng-Ying Lin; Tina Ting-Xia Dong; Ran Duan; Qi-Wei Qin; Wen-Xiong Wang; Karl Wah-Keung Tsim (Aquaculture, 2023)

In vitro and in vivo anti-tumor activity of Antrodia salmonea against twist-overexpressing HNSCC cells: Induction of ROS-mediated autophagic and apoptotic cell death - Hsin-Ling Yang; Yi-An Lin; Sudhir Pandey; Jiunn-Wang Liao; Tzong-Der Way; Yu-lyu Yeh; Siang-Jyun Chen; You-Cheng Hseu (Food and Chemical Toxicology, 2023)

Behavioral and transcriptomic changes in butenolide treated larvae of the cosmopolitan fouling bryozoan Bugulina (Bugula) neritina - Jin-You Liang; Yi-Fan Cheng; Xiao-Lin Huang; Ying Xu; Yue Him Wong; Yu Zhang (Frontiers in Marine Science, 2022)
The arborescent bryozoan Bugulina neritina is a cosmopolitan fouling species in sub-tropical to sub-temperate waters. The butenolide compound 5-octylfuran-2(5H)-one (hereafter named butenolide) reportedly inhibits larval settlement of B. neritina , but its effect on the larval behavioral and transcriptomic responses remained unclear. We report that 10 μg mL -1 or higher concentration of butenolide and/or prolonged treatment (10 h or longer) resulted in significant increase in larval mortality and prominent spiral larval swimming behavior. The transcriptomic analyses not only revealed up-regulation of typical stress-related protein genes in response to 10 mg mL -1 butenolide treatment, but also indicated up-regulation of mucin , synaptic genes and nitric oxide signaling genes. In addition, the expression of developmental genes and lipid biosynthesis genes were also affected. Overall, our larval behavior and transcriptome analyses reflected the impact of butenolide on the metabolism, neuronal and molecular signaling in B. neritina larvae.

Extensive sequence divergence between the reference genomes of Taraxacum kok-saghyz and Taraxacum mongolicum - Tao Lin; Xia Xu; Huilong Du; Xiuli Fan; Qingwen Chen; Chunyan Hai; Zijian Zhou; Xiao Su; Liquan Kou; Qiang Gao; Lingwei Deng; Jinsheng Jiang; et al. (Science China Life Sciences, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Comparative physiological and proteomic analyses of mangrove plant Kandelia obovata under cold stress - Jiao Fei; You-Shao Wang; Hao Cheng; Fu-Lin Sun; Cui-Ci Sun (Ecotoxicology, 2021)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

A comparison of hepatotoxicity induced by different lengths of tungsten trioxide nanorods and the protective effects of melatonin in BALB/c mice - Lin Mao; Lifang Zheng; Huihui You; Muhammad Wajid Ullah; Haoyan Cheng; Qing Guo; Zhihong Zhu; Zhuge Xi; Rui Li (Environmental Science and Pollution Research, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

A calculation model to assess the crack propagation length of rock block in clastic flow - Yang Liu; Yong You; Jin-feng Liu; Shu-xi Zhao; Dong-xu Yang; Dao-chuan Liu; Lin Liu; Yan-fang Xie; Kai-cheng Yang (Journal of Mountain Science, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Nanochemoprevention with therapeutic benefits: An updated review focused on epigallocatechin gallate delivery - Qiong-Qiong Yang; Xin-Lin Wei; Ya-Peng Fang; Ren-You Gan; Min Wang; Ying-Ying Ge; Dan Zhang; Li-Zeng Cheng; Harold Corke (Critical Reviews in Food Science and Nutrition, 2020)

Impacts of elevated temperature and pCO2 on the brooded larvae of Pocillopora damicornis from Luhuitou Reef, China: evidence for local acclimatization - Lei Jiang; Ming-Lan Guo; Fang Zhang; Yu-Yang Zhang; Guo-Wei Zhou; Xin-Ming Lei; Xiang-Cheng Yuan; You-Fang Sun; Tao Yuan; Lin Cai; Jian-Sheng Lian; Sheng Liu; et al. (Coral Reefs, 2020)

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

Conditional Overexpression of rtn4al in Muscle of Adult Zebrafish Displays Defects Similar to Human Amyotrophic Lateral Sclerosis - Cheng-Yung Lin; Po-Hsiang Zhang; You-Jei Chen; Chia-Lun Wu; Huai-Jen Tsai (Marine Biotechnology, 2019)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Evaluation of Lactic Acid Bacteria Isolated from Fermented Plant Products for Antagonistic Activity Against Urinary Tract Pathogen Staphylococcus saprophyticus - Cheng-Chih Tsai; Tzu-Min Lai; Pei-Pei Lin; You-Miin Hsieh (Probiotics and Antimicrobial Proteins, 2018)

Comparative Transcriptome Analysis Provides Insights into Differentially Expressed Genes and Long Non-Coding RNAs between Ovary and Testis of the Mud Crab (Scylla paramamosain) - Xiaolong Yang; Mhd Ikhwanuddin; Xincang Li; Fan Lin; Qingyang Wu; Yueling Zhang; Cuihong You; Wenhua Liu; Yinwei Cheng; Xi Shi; Shuqi Wang; Hongyu Ma (Marine Biotechnology, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Three-dimensional shallow velocity structure beneath Taal Volcano, Philippines - Shuei-Huei You; Konstantinos I. Konstantinou; Yuancheng Gung; Cheng-Horng Lin (Journal of Seismology, 2017)

Chalcone flavokawain B induces autophagic-cell death via reactive oxygen species-mediated signaling pathways in human gastric carcinoma and suppresses tumor growth in nude mice - Chia-Ting Chang; You-Cheng Hseu; Varadharajan Thiyagarajan; Kai-Yuan Lin; Tzong-Der Way; Mallikarjuna Korivi; Jiuun-Wang Liao; Hsin-Ling Yang (Archives of Toxicology, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Ceramics manufacturing contributes to ambient silica air pollution and burden of lung disease - Chung-Min Liao; Bo-Chun Wu; Yi-Hsien Cheng; Shu-Han You; Yi-Jun Lin; Nan-Hung Hsieh (Environmental Science and Pollution Research, 2015)

Distribution and sources of the polycyclic aromatic hydrocarbons in the sediments of the Pearl River estuary, China - Jian-Dong Zhang; You-Shao Wang; Hao Cheng; Zhao-Yu Jiang; Cui-Ci Sun; Mei-Lin Wu (Ecotoxicology, 2015)

Variation of phytoplankton community structure from the Pearl River estuary to South China Sea - Zhao-Yu Jiang; You-Shao Wang; Hao Cheng; Cui-Ci Sun; Mei-Lin Wu (Ecotoxicology, 2015)

Pb uptake and tolerance in the two selected mangroves with different root lignification and suberization - Hao Cheng; You-Shao Wang; Yong Liu; Zhi-Hong Ye; Mei-Lin Wu; Cui-Ci Sun (Ecotoxicology, 2015)

Spatial and vertical distribution of bacterial community in the northern South China Sea - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Hao Cheng (Ecotoxicology, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Seasonal characteristics and tetrodotoxin-producing ability of bacteria in gastropod Oliva hirasei - Chun-Lan Lin; Ya-Jung Wu; Wen-Feng Lin; Cheng-Hong Hsieh; You-Liang Hsieh; Deng-Fwu Hwang (Hydrobiologia, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Landslides and catchment sedimentation in the Ta-Chia River influenced by the 1999 Taiwan Chi-Chi earthquake - Keh-Jian Shou; Li-Yuan Fei; Jiin-Fa Lee; Cheng-Yueh Wei; Sheng-Tsi Huang; You-Chang Lin (International Journal of Remote Sensing, 2012)

Co-occurrence of arseniasis and fluorosis due to indoor combustion of high fluorine and arsenic content coal in a rural township in northwest China: epidemiological and toxicological aspects - Guo-fang Lin; Shi-you Gong; Cheng Wei; Ji-gang Chen; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Quantitative Analysis of Quercetin in Euphorbia helioscopia L by RP-HPLC - Hai Peng Liu; Xiao Feng Shi; You Cheng Zhang; Zhong Xin Li; Lin Zhang; Zhe Yuan Wang (Cell Biochemistry and Biophysics, 2011)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Genome-wide analysis of microsatellite sequence in seven filamentous fungi - Cheng-Yun Li; Lin Liu; Jing Yang; Jin-Bin Li; Yuan Su; Yue Zhang; Yun-Yue Wang; You-Yong Zhu (Interdisciplinary Sciences: Computational Life Sciences, 2009)